Assessment of Total Dissolved Solids Variation and Its Impact on Water Quality in the Euphrates River Using GIS Techniques (Texas Journal of Multidisciplinary Studies, 2025)
Evaluation of the Variation of Total Dissolved Solids (TDS) and Its Effect on the Water Quality of the Euphrates River in Southern Iraq Using GIS Techniques The Euphrates River has been heavily polluted from industrial discharge, agricultural runoff, and a rapidly expanding population, and is a vital freshwater source for Iraqi people. All Data from five monitoring stations (Babil, Qadisiya, Muthanna, Dhi Qar, and Basra) for the for years 2019–2021 The datasets were analyzed through Microsoft Excel and ArcGIS to determine the temporal and spatial distribution of the TDS concentrations and the pollution source hotspots. Results demonstrate that the highest TDS therefore the highest salinity and poor water quality compared to World Health Organization (WHO) and Food and Agriculture Organization (FAO) standards was AlNasiriyah within Dhi Qar Province.